Leadership Performance and Rhetoric - Masters, Adam B. author. aut Link
XIII, 153 p. 4 illus.
Keywords: ‘Words are actions, and leaders know it. This thought-provoking study sheds light on the rhetorical battles that have shaped Australia’s recent political history – and it’s a cracking good read to boot.’ – Dr Dennis Grube, University of Cambridge, UK This book examines both the rhetorical content of contemporary public leadership and the leadership methods pioneered by early English statesman Sir Francis Bacon. In particular, it considers the use of public rhetoric to defend leadership legitimacy in six case studies, drawing on leadership contests in recent Australian political history. The authors map out the complex language of leadership in contemporary politics through chapter-length portraits of the inter-related political rhetoric of prime ministers Rudd, Gillard, Abbott and Turnbull, plus former foreign minister Bob Carr and indigenous leader Noel Pearson. The process is a novel application of leadership analysis derived from the politicalphilosophy of Francis Bacon, who emerges as a founder of the study, and indeed practice, of political and public leadership. The book will appeal to students and scholars across the fields of political science, communication and rhetorical studies, and political history.